Individual characteristics and innovation performance in SMEs: Moderating role of psychological capital - Saima Aziz (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: This research aimed to identify the individual characteristics and innovation performance in Pakistani SMEs, as well as the moderating role of psychological capital. Specifically, the present research used organizational behavior theory and social exchange theory. Methodology: To analyze the data, 310 SME managers in Pakistan filled out an online survey. Structural Equation Modeling (SEM) results indicate that emotional investment favors adaptability. Findings: Additionally, the results demonstrated the moderating role of psychological capital in the relationship between change readiness and affective commitment, creativity, and trust in Pakistani SMEs. Implications/Novel Contribution: Another significant contribution is the study’s use of organizational behavior theory and social exchange theory. Managers can improve staff retention by instituting policies that build a sense of belonging, respect for management, and pride in one’s work. This research adds to what was previously known about the innovation simulation platform in Pakistan’s S MEs.